A Need Analysis of English Learning for Elementary School - Nur Qonita Aulia; Albiansyah Albiansyah (Musamus Journal of Language and Literature, 2021)
Abstract Many people agree that English is an essential language because English is an international language. In Indonesia, students learn English since they are at kindergarten and primary level, and we can call them young learners. This study is going to find students need analysis Of English Learning For Elementary Schools. In this study, the researcher used a qualitative descriptive method and data presentation as supporting data. This study's participant is students from fourth-grade elementary school at MIS Al – Mujahidah Bogor Regency. To get the data, the researcher use questionnaire and documentation (Textbook) as an instrument. This study shows the students interested in the book containing animated cartoon and games or interactive activity for them. The textbook that is not emphasized to the student’s elementary school age can be an obstacle or the difficulties for students to learn English. It can make the students not interested to learn English. So, the institution needs to double-check before choosing students textbooks because there is some deficiency in the book that makes it difficult for students to learn. Keywords: Need Analysis, English Young Learner, Learning material, Elementary School